Representation of Popular Islamic Movements on Social Media: A Study of the Hashtag #LogIndiCloseTheDoor - Muhammad Arman Al Jufri; Ahmad Tsaaqib; Agus Rahman Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
This article an discusses the Ramadan podcast series Hashtag #LogIndiCloseTheDoor as an example of the Popular Islamic Movement on social media. The series was a huge hit even though it dealt with a delicate subject. It is impossible to consider this truth to be a phenomenon deserving of the widespread success of social media material. This article is a qualitative study employing Talal Asad's Islamic Anthropology method. According to the article's conclusion, the Popular Islam Movement is a group of middle-class Muslims, particularly those in their millennial years, who are using modern and popular culture as a means of self-actualization and self-study. The media portrays him in two ways: dakwahtainment and religiotainment. Ramadan's audio series #LogIndiCloseTheDoor is one of them. The Islamic pretext Raḥmatan lil 'Ālamīn (a mercy to all creation) serves as the basis for the television show. The discussion that goes along with this series focuses on inclusivism in religion as well as the commoditization and commodification of religion. These discourses were communicated and developed into a new religious paradigm by way of the power relations network that Deddy Corbuzier, Habib Ja'far Hussein, and Leonardo da Vinci constructed. This essay contends that the #LogIndiCloseTheDoor Ramadan Hashtag audio series, which combines modern and Islamic ideals, transforms the initially conservative, restrictive, and inflexible perception of Islam into one that is inclusive, tolerant, and dynamic.